La nueva legislación educativa: por qué no mejorará la educación pública en España - Azcárraga, José Adolfo de (Revista Española de Pedagogía, 2023)
Se exponen algunas razones por las que, en opinión del autor, el reciente afán legislativo de las autoridades educativas españolas que afecta a la enseñanza primaria, la secundaria, al bachillerato y a las universidades, no mejorará la calidad de la enseñanza en España.
The new Spanish educational legislation: why public education will not improve
This paper provides some reasons that explain, in the view of the author, why the present eagerness of the Spanish Educational Authorities to reform all levels of education, from primary school to the universities, will not improve the quality of the Spanish educational system.
Keywords: próxima legislación educativa española; educación primaria; educación secundaria; universidades; Forthcoming Spanish educational legislation; primary school; secondary education; universities; Revista Española de Pedagogía